2006
DOI: 10.1039/b606370e
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast excited state proton transfer dynamics of 1,2-dihydroquinolines in methanol solution

Abstract: Femtosecond and picosecond dynamics of 2,2,4,6-tetramethyl-1,2-dihydroquinoline (1) and 1,2,2,4,6-pentamethyl-1,2-dihydroquinoline (2) were studied in MeOH, MeOD, and Pr(i)OH to probe the early events of the photoinduced proton transfer (PT) between 1,2-dihydroquinolines (DHQ) and a solvent. From studies in the two solvents MeOH and Pr(i)OH and by examining the effect of deuterium replacement of proton, it has been established that PT takes 150-200 fs in MeOH, but does not occur in Pr(i)OH. The formation of PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Currently, many efforts are devoted to investigating photochemical and photophysical process of ESIPT of small molecules. [8][9][10][11][12][13] As compared with small size molecules, the relative large molecular design and exhausted computation are always great challenges for chemists, the investigation of ESIPT of such molecules is extremely lower than their application potentials in various fields, and only a few studies on ESIPT of these molecules were reported. For instance, aggregationinduced ESIPT emission enhancement of some molecules was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many efforts are devoted to investigating photochemical and photophysical process of ESIPT of small molecules. [8][9][10][11][12][13] As compared with small size molecules, the relative large molecular design and exhausted computation are always great challenges for chemists, the investigation of ESIPT of such molecules is extremely lower than their application potentials in various fields, and only a few studies on ESIPT of these molecules were reported. For instance, aggregationinduced ESIPT emission enhancement of some molecules was observed.…”
Section: Introductionmentioning
confidence: 99%
“…9 The photo dynamics of intermolecular proton transfer in the 1,2 dihydroquinoline-MeOH system was studied. Intermolecular proton transfer involving a non relaxed vibrationally excited state was observed experimentally.…”
Section: Femtochemistry Of Elementary Reactionsmentioning
confidence: 99%
“…29 This stepwise dynamics of the transient absorbance after the femtosecond pulse with λ pump = 350 nm crucially differs from the dynamics observed for λ pump = 308 nm, when the PT reaction was completed to the time delay of 200−500 fs. 17 It should be emphasized that, whatever the excitation wavelength is, the final product 1,2,3,4-tetrahydroquinoline is formed quantitatively, indicating that the nature of final transient species generated as a result of the PT reaction does not depend on the excitation wavelength. The results obtained set two main problems which should be considered: (i) the cause of the difference in PT dynamics at different excitation wavelengths and (ii) interpretation of the stepwise dynamics for λ pump = 350 nm.…”
Section: ■ Introductionmentioning
confidence: 99%